Psycho-Social-Environmental Factors Associated with Work-Related Stress in Chilean Teachers in Rural and Urban Areas - Rubio-González, Juan (2019)
The aim of this study was to investigate the perceptions that teachers in urban and rural schools have of the psycho-social-environmental factors that trigger teacher work stress. Considering a phenomenological qualitative approach, with exploratory scope, a case study design is used with teachers from the locality of Collipulli, southern Chile, with a Discussion Group technique to collect data and content analysis, from which it can be inferred that teachers tend to perceive that environmental factors such as deficient leaderships, undetermined teaching roles, work overload, overcrowded classrooms, unmotivated students, and disconnection of parents from their educational role, would be the main threats to their mental health. The psychological resources, coping styles and context perception presented by the teachers in the study are discussed.